Detailed demographic analysis of an Epinephelus polyphekadion spawning aggregation and fishery - Rhodes, K.; Taylor, B.; McIlwain, Jennifer (Inter-Research, 2011)
The demographic profile of camouflage grouper Epinephelus polyphekadion (Bleeker, 1849), a widely distributed, commercially important, and Near Threatened (on the IUCN Red List) reef fish species, was established in the present study by sampling markets and a spawning aggregation in Pohnpei, Micronesia. Estimates of size at age, growth, and mortality were obtained from sectioned sagittal otoliths. Sections showed clear annuli whose formation coincided with decreasing, low-variability seawater temperature. Mean size, age, or growth rates did not differ between sexes. The maximum age (tmax) was 22 yr. Estimated growth and mortality parameters resembled those of other tropical epinephelines that display low population turnover (instantaneous growth coefficient [K] = 0.251 yr–1; total mortality [Z] = 0.227 yr–1; and natural mortality [M] = 0.144 yr–1). Juveniles recruited to the fishery at Age 2, but adults were not present in the aggregation until Age 4. The sexual pattern for this species was resolved by complementing detailed histological analyses with age data to show functional gonochorism with the potential for protogynous sexual transition. Following intense aggregation fishing in 1999, females averaged 30 mm less in size and nearly 3 yr younger than those caught in 1998. Since 1999, aggregation abundance has declined from several thousand to a few hundred individuals and a significant mean size reduction has been detected in marketed samples. Relative to other regional locales, camouflage grouper in Pohnpei has a substantially truncated age and size structure, all suggesting that the species is experiencing fisheries-induced demographic changes. Proactive and adaptive management is needed to reduce the perceived impacts to spawning adults and juveniles and improve spawning stock biomass.